2016
DOI: 10.1063/1.4963273
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of interface abruptness and In content in (In,Ga)N/GaN superlattices

Abstract: We investigate designed InN/GaN superlattices (SLs) grown by plasma-assisted molecular beam epitaxy on c-plane GaN templates in situ by line-of-sight quadrupole mass spectroscopy and laser reflectivity, and ex situ by scanning transmission electron microscopy, X-ray diffraction, and photoluminescence (PL). The structural methods reveal concordantly the different interface abruptness of SLs resulting from growth processes with different parameters. Particularly crucial for the formation of abrupt interfaces is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…However, the mechanism of In x Ga 1−x N growth from an intermetallic adlayer is in contrast to our observations: in both sample series A and B, the amount of indium present in the adlayer under metal-rich conditions at the beginning of the GaN deposition stage is at least 2 MLs. Furthermore, excess indium inside surface droplets is sufficiently mobile at 610 °C to wet the surface, providing an extra indium reservoir 44 . Therefore, it would be expected that growth from the In-Ga intermetallic adlayer would result in QWs thicker than 1–2 MLs and/or with a diffuse upper interface.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism of In x Ga 1−x N growth from an intermetallic adlayer is in contrast to our observations: in both sample series A and B, the amount of indium present in the adlayer under metal-rich conditions at the beginning of the GaN deposition stage is at least 2 MLs. Furthermore, excess indium inside surface droplets is sufficiently mobile at 610 °C to wet the surface, providing an extra indium reservoir 44 . Therefore, it would be expected that growth from the In-Ga intermetallic adlayer would result in QWs thicker than 1–2 MLs and/or with a diffuse upper interface.…”
Section: Discussionmentioning
confidence: 99%
“…In the first set of in-situ experiments, the Mg, In, and N fluxes were supplied in different orders on a GaN(0001) template while line-of-sight QMS 19 was utilized to measure the desorption signal of 69 Ga, 115 In, 24 Mg, 25 Mg, and 26 Mg from the substrate surface. However, for the 69 Ga, 24 Mg, 25 Mg, and 26 Mg signals monitored by QMS, no change was observed due to the relatively low growth temperature, and the shadowing effect by the 28 the N shutter induced a change in the partial pressure and it yielded an offset in the record of the desorption signal of all species that were supplied or not.…”
Section: Methodsmentioning
confidence: 99%
“…The second set of experiments consisted of (In,Ga)N/GaN SLs formed with 10 repeats of ( 20MLs InN/ 40 MLs GaN) sequences supplied at 610 °C following the approach described in ref. [19], where Mg was inserted at a different time in the sequence for each sample. Note that former studies have shown that the deposition of thick binary InN QWs at such high growth temperature yield actually QWs with a self-limited thickness of 1 ML of (In,Ga)N and a maximum In content of 0.33 [18][19][20][21] .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations